2004
DOI: 10.1002/hep.20271
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular telomere shortening correlates with chromosomal instability and the development of human hepatoma

Abstract: The telomere hypothesis of cancer initiation indicates that telomere shortening initiates cancer by induction of chromosomal instability. To test whether this hypothesis applies to human hepatocellular carcinoma (HCC), we analyzed the telomere length of hepatocytes in cytological smears of fine-needle biopsies of liver tumors from patients with cirrhosis (n ‫؍‬ 39). The tumors consisted of 24 HCC and 15 regenerative nodules as diagnosed by combined histological and cytological diagnostics. In addition, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
90
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 26 publications
5
90
2
2
Order By: Relevance
“…However, the meaning of telomere length is a complicated subject. While it has been shown that telomere length correlates inversely, and telomerase activity directly, with malignancy in epithelial tumors, [6][7][8][9] only a couple of studies address this question in soft tissue tumors. 22,23 Bonatz et al measured telomere length in 107 uterine leiomyomas using a Southern blot method and found that telomeres were significantly shorter in tumoral tissue compared to adjacent uterine smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the meaning of telomere length is a complicated subject. While it has been shown that telomere length correlates inversely, and telomerase activity directly, with malignancy in epithelial tumors, [6][7][8][9] only a couple of studies address this question in soft tissue tumors. 22,23 Bonatz et al measured telomere length in 107 uterine leiomyomas using a Southern blot method and found that telomeres were significantly shorter in tumoral tissue compared to adjacent uterine smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, since there is a 50% chance that the same X-inactivation could occur incidentally between two tumors, more cases should be analyzed using this method. Telomere shortening, a possible crucial event leading to chromosomal instability and development of malignancy, has been reported in multiple types of human cancer [6][7][8][9] and can be demonstrated with telomerespecific fluorescence in situ hybridization (FISH) probes.…”
mentioning
confidence: 99%
“…17 Telomere length becomes shorter in the early stages of human hepatocarcinogenesis, 18,19 and these short telomeres are thought to be one of the factors that can induce chromosomal instability, an important mechanism of HBV-related hepatocarcinogenesis. 20,21 Epigenetic modification has been implicated as a critical event in carcinogenesis. 22 Aberrant DNA methylation of proto-oncogenes and tumor suppressor genes has frequently been found in human cancers.…”
mentioning
confidence: 99%
“…3 We have recently demonstrated that telomere shortening characterizes hepatocytes of HCC compared with hepatocytes in regenerative nodules or surrounding noncancerous liver tissue. 8 Whether telomere shortening simply leads to random genomic instability or whether it leads to specific cytogenetic changes reflecting the cytogenetic fingerprint of a specific tumor type remains to be determined. In more than 90% of all HCC, chromosomal aberrations can be detected by using centromere-specific chromosome probes for chromosomes 1 and 8, indicating the significant role of CIN in the development of HCC.…”
mentioning
confidence: 99%